Análise das variáveis do processo para obtenção de compósito bronze-quasicristal - Andrade, Erick Thiago Costa de (2022)
In the industrial environment there is an intense search for materials with better performance than the materials already on the market, this makes research in this direction very interesting, one of the most used aspects in this area is the production of composite materials, a type that has been gaining a relevant importance are the copper-based metal matrix composites, however, due to their low mechanical strength, which prevents their use in some technological areas, a matrix of highly conductive copper alloys needs to be reinforced, causing the appearance of new composite materials with superior characteristics. This work aimed at the production of a composite with a bronze matrix reinforced with quasicrystalline particles of AlCuFe through the powder methodology, aiming at the study of process variables and degree of importance in the formation of the intended material. In order to obtain the samples, a factorial design of 23 was carried out, that is, there was a variation of parameters, force applied in the compaction, the sintering temperature and the fraction of the reinforcement inside the matrix, thus being able to carry out a study for each sample seeking the best situation among them. The green density, the relative density of the green and sintered specimens, the porosity of the samples were analyzed and microscopy images of the samples with higher and lower degree of porosity were made. Through this work, it was possible to obtain composites of bronze matrix reinforced with quasicrystal, in addition, it was possible to use the sintering temperature of the specimens to promote the heat treatment of the AlCuFe alloy for the appearance of the quasicrystalline phase, thus eliminating a step in the process.